Dynamics of Urban Transport Arrangement Policies to Support the Achievement of Sustainable Transportation - Muhammad Eko Atmojo; Awang Darumurti; Nita Aribah Hanif; Muhammad Wahyu Agani (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2024)
This article analyses the dynamics of the transport policy of the government of Yogyakarta, Indonesia, and the administration’s efforts to organise transportation for sustainability. A qualitative method with a case study approach is used in the research. For data analysis, an interactive model and NVivo 12 Plus qualitative data analysis software were used. The results suggested several initiatives that the government of Yogyakarta must undertake to implement sustainable transportation, including transportation policies, infrastructure development and public awareness. The Yogyakarta government does not yet have regulations that form the basis for the implementation of sustainable transportation in the region. Sustainable transport has only recently become a developmental priority in the 2020–2024 regional mid-term development plan, which reflects the Indonesian government’s lagging in promoting sustainable transport on a national and regional scale. For sustainable transport infrastructure, the government of Yogyakarta has operated the rapid bus system Trans Jogja for public transport. However, the implementation of Trans Jogja has been suboptimal because it is considered unable to meet the needs of the community and forces the people of Yogyakarta to use private vehicles for daily mobility. Therefore, The Yogyakarta government is currently working on electric energy-based public transportation (electromobility), which is more environmentally friendly as it does not use fuel oil and has low emissions.